Usability of Lampung Heritage Virtual Reality Tour - Sony Ferbangkara; Mardiana Mardiana; F.X. Arinto; Sri Ratna Sulistiyanti; Khairudin Khairudin; Wahyu Eko Sulistiono; Meizano Ardhi Muhammad (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2022)
Lampung Heritage Virtual Reality Tour was developed as a tool to educate the importance of Lampung’s historical heritage. It represents eight Lampung historical heritage sites in the virtual reality world, namely the Lampung Museum, Thay Hin Bio Vihara, Al-Anwar Mosque, Lampung Siger Tower, Krakatau Monument, Kerti Bhuana Temple, Nuwo Sesat Traditional House, and the Japanese Caves. Functional features of the Lampung Heritage Virtual Reality Tour are visiting virtual tourist spots and viewing information on virtual tourist attractions. Digital tourists can select a virtual tourist spot with the location panel. The user perception and satisfaction require a qualitative measurement to understand its impact on educating Lampung's historical heritage. Using usability, we should understand the quality of the Lampung Heritage Virtual Reality Tour. The tools to measure the usability level of the application are the User Acceptance Test and the System Usability Scale. There were 15 questions User Acceptance Test (UAT) with a composition of five questions affordance, four questions signifier, and six questions feedback. According to the SUS standard, we asked ten questions on the System Usability Scale (SUS). The result for UAT was an average of 95.75%, which consist of 95.00% affordance, 94.79% signifier, and 97.45% feedback. The result of SUS was Good, based on a score of 83.39. The Lampung Heritage Virtual Reality Tour meets good usability standards, making the application suitable.